Quality of Life and Sexual Function of Placenta Accreta Spectrum Disorder Patients after Surgery - Muara P. Lubis; Melvin N.G. Barus; M Rizki Yaznil; Edwin M. Asroel; Irwin L. Lumbanraja (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: To evaluate sexual function and quality of life features using two validated Female Sexual Function Index (FSFI) questionnaires, and the Short-Form Health Survey (SF-36) in patients with sexually active on Placenta Accreta Spectrum (PAS) Disorder patient.Method: This research is a cross sectional analytic observational study which was conducted in Haji Adam Malik General Hospital from January 2017 - December 2019. Thirty-five study patients who have been diagnosed with PAS disorder and have been treated for at least 3 months were divided into hysterectomy and conservative groups. This study data consisted of primary data from interviews and secondary data from medical records. Independent T test is used if it is normally distributed and Mann-Whitney is used if it is not normally distributed, and it is declared significant if the P value is <0.05. Result: From 8 assessment variables in the SF-36 questionnaire by comparing the questionnaire scores of PASD patients in the hysterectomy and conservative groups by showing significant results on social function (P value 0.021). Whereas in the FSFI questionnaire, there were 6 variables to assess the sexual function of patients with pain variable showing significant results (P value 0.007).Conclusion: There were differences in quality of life (social function) and sexual function (pain) in PASD patients in the hysterectomy and conservative groups.Keywords: Female Sexual Functional Index, Placenta Accreta Spectrum, Quality of Life, Short-Form Health Survey. Abstrak Tujuan: Untuk mengevaluasi fungsi seksual dan fitur kualitas hidup dengan menggunakan dua kuesioner tervalidasi Female Sexual Function Index (FSFI), dan Short-Form Health Survey (SF-36) pada pasien dengan placenta accrete spectrum (PAS) disorder yang aktif secara seksual setelah tindakan operasi.Metode: Penelitian ini merupakan penelitian analitik observasional dengan metode potong lintang yang dilaksanakan di Rumah Sakit Umum Haji Adam Malik dari January 2017-December 2019. Tiga puluh lima pasien yang didiagnosis dengan plasenta akreta spectrum dan telah ditatalaksana minimal 3 bulan dibagi menjadi kelompok histerektomi and konservatif. Data penelitian ini terdiri atas data primer dari wawancara dan data sekunder dari rekam medis. Uji T independen digunakan jika berdistribusi normal dan Mann-Whitney digunakan jika tidak berdistribusi normal, serta dinyatakan signifikan jika nilai P <0.05.Hasil: Dari 8 variabel penilaian dalam kuesioner SF-36 dengan membandingkan skor kuesioner pasien PASD pada kelompok histerektomi dan konservatif dengan menunjukkan hasil yang signifikan pada fungsi sosial (nilai P = 0,021). Sedangkan dalam kuesioner FSFI terdapat 6 variabel untuk menilai fungsi seksual pasien dengan variabel nyeri yang menunjukkan hasil yang signifikan (nilai P = 0,007).Kesimpulan: Terdapat perbedaan dalam kualitas hidup (fungsi sosial) dan fungsi seksual (nyeri) pada pasien PASD di kelompok histerektomi dan konservatif. Kata Kunci: female sexual functional index, placenta accreta spectrum, quality of life, short-form health survey.